The Effect of Non-Sharia Financial Instruments on Indonesian Economic Growth - Sandi Mulyadi; Asep Suryanto (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The purpose of this study was to determine and analyze the impact and contribution of the non-bank financial industry (IKNB) and non-Islamic banking on Indonesia's economic growth before and during the pandemic. The variables used in this study are data on total assets of Sharia IKNB, IKNB, and Industrial Production Index (IPI) data as a measure of economic growth. The research method used is the Vector Error Correction Model (VECM) method using monthly time series data from 2015 to 2021. The research results reveal several results, the long-term VECM test of Islamic NBFI and NBFI variables has an impact on economic growth, while the IRF test shows that economic growth is resistant to shocks by sharia NBFIs and NBFIs over the next 60 years, contributing 11% and 4% to economic growth, respectively.